Exploitation of Germplasm for Plant Yield Improvement in Cotton (Gossypium hirsutum L.) (Journal of Green Physiology, Genetics and Genomics, 2015)
Diverse genetic resources are vital for ample production for imminent challenges. The current study was aimed to find pattern of genetic diversity among 50 cotton genotypes and selection of diverse genotypes for upcoming cotton breeding programs. Data was recorded for fourteen quantitative attributes. All attributes exhibited tinny difference phenotypic coefficient of variation (PCV) and respective genotypic coefficient of variation (GCV), suggesting that environment had less effect on all the recorded attributes. High expected genetic advance coupled with higher heritability (broad sense) were recorded for plant height, number of bolls per plant, weight per boll and plant yield, indicating the existence of additive gene action hence selection on phenotypic basis might be productive. Correlation studies revealed positive and significant association for most of the attributes. Plant height, number of monopodia and sympodia/plant, and number of bolls/plant contributed well towards considerable principal components (PCs) and were highly related to plant yield (seed cotton yield per plant). The projection of cotton genotypes on 1st and 2nd PC exhibited population structure. Best diverse genotypes were IUB-222, SB-149, CIM-612, CIM-598, CIM-506, RS-1 and VS-1. The outcomes for this experiment are helpful for planning forthcoming cotton breeding programs particularly in Pakistan.
Keywords: Biodiversity, Principal component analysis, Phenotypic coefficient of variation, Genotypic coefficient of variation, Heritability